Numerically study of CH4/NH3 combustion characteristics in an industrial gas turbine combustor based on a reduced mechanism. (1st November 2022) - Sun, Jihao; Yang, Qiang; Zhao, Ningbo; Chen, Mingmin; Zheng, Hongtao
Highlights: Detailed and reduced methane/ammonia combustion mechanisms for gas turbines are proposed. Methane/ammonia combustion in an industrial gas turbine combustor is numerically studied. Increasing fuel's ammonia content will lead to a longer, thinner, higher lifted flame. For methane/ammonia combustion in this combustor, combustion will not occur at ϕ < 0.5. The flame is no longer "V-shaped" when ammonia fraction in the fuel is above 0.3. Abstract: This study numerically investigated ammonia/methane combustion characteristics (e.g. flame structure, temperature and species field) and velocity field in an industrial DLN gas turbine combustor with ammonia mass fraction up to 70%. To ensure accuracy and efficiency, a detailed mechanism based on GRI-Mech 3.0 and Otomo model was firstly assembled and then reduced via DRGEP and sensitive analysis. Both mechanisms show good performance for ignition delay and laminar flame speed calculation under gas turbine combustors' working conditions. Numerical results of the combustor show that when fuel's ammonia ratio is above 0.3, the flame is no longer "V-shaped", increasing ammonia fraction in the fuel will lead to a longer, thicker, higher lifted flame. However, velocity field and combustion efficiency are not sensitive to fuel's ammonia content. Combustion of ammonia/methane will not occur at ϕ < 0.5 in the combustor. Methane and ammonia consumption regions are at the same position, and NOx can form upstream of the flame front. With the increase of ammonia fraction in the fuel, an opposed effect was found for OH and HNO concentration, this leads NOx emissions to increase first and then decrease.